Identifying Christian Values-Based Entrepreneurship Opportunities in Christian Education in the Digital Age - Afriani Manalu (PT FORMOSA CENDEKIA GLOBAL, 2026)
This study aims to identify Christian values-based entrepreneurship opportunities in Christian Religious Education (PAK) in the digital age. The approach used is qualitative with a conceptual paper method that emphasizes analysis, synthesis, and reflection on the sources of Christian theology, education, and modern entrepreneurship. The results of the study show that entrepreneurial opportunities in PAK can be developed through digital innovation, church-based community strengthening, social mission-based education, and the integration of faith values in the learning process. Entrepreneurship in this perspective is not only understood as an economic activity, but also as an expression of faith and a vocation within the framework of the missio Dei. This study resulted in a conceptual model of Faith–Context–Innovation (FCI) that integrates faith, context analysis, and innovation as a whole in developing Christian entrepreneurship in education.